Mapping Islamic Social Finance’s Impact on SDGs: A Bibliometric Dive into Decent Work and Economic Growth - Khoirun Nisak (Niqosiya: Journal of Economics and Business Research, 2024)
Introduction: The SDGs are goals that countries around the world want to achieve by 2030. However, this bis project requires a lot of funding. So it requires other alternative funding such as Islamic social finance. This research wants to examine the funding of SDGs, especially goal number 8 using Islamic social finance instruments. Research Methods: This study adopts a bibliometric approach by analyzing 500 articles published between 2015 until 2024 using Publish or Perish, which were sourced from Google Scholar. Based on their focus on Islamic social finance and the SDGs number 8, 25 relevant articles were selected from this initial pool. Keyword analysis, network visualization, and density mapping were performed using VOSviewer software. Examining keyword occurrences and temporal overlaps helped to identify dominant themes, gaps, and emerging areas of focus in Islamic social finance research. Result: The results show that zakaf and waqf are the most frequently discussed topics. This underscore their central role in aligning Islamic financial principles with SDGs. However, instruments such as sadaqah, qard al-hasan, and takaful continue to be under-explored, pointing to significant gaps in the literature. Conclusions: As a recommendation, to fully understand their potential contributions to the SDGs number 8, further research on other Islamic social finance instruments beyond zakat and waqf is needed.